Repurposing drugs in endometrial cancer using genomic variants database - Darmawi, Darmawi; S, Donel; Suhandri, Wiwin; Winarto, Winarto; Adikusuma, Wirawan; Irham, Lalu Muhammad; Fidiawati, Wiwit Ade; Razali, Renardy Reza; Nathania, Auren; Zahra, Leina Putri (Pharmaciana, 2023)
Endometrial cancer (EC) is the fourth most frequent gynecological cancers, and its incidence and mortality rates have increased over the last decade. Cytotoxic therapy with carboplatin and paclitaxel is the recommended first-line treatment for EC patients. However, the options for following therapy are limited. The latest advances in molecular studies have uncovered the nature of genetic alterations in EC, compelling methods for further research into the treatment of EC since they may disclose to tailored pharmacological therapy. The aim of this study to identify novel drug candidates in treating EC using genomics variants and biological pathway. The genomic variants of  EC were downloaded from cBioportal database. We established connection between the biological EC risk genes from cBioportal database and the DrugBank database. Finally, we used Connectivity Map (CMap) analysis to identify possible drugs whose mechanisms coincided with therapeutic targets and rank them based on the scoring system. We identified novel potential candidate drugs for EC, they are Bosutinib and Nilutamide which exhibit robust scores in the CMap analysis compare to paclitaxel. We also discovered BCR-ABL1 and AR as potential biomarker-driven therapy in EC. This study demonstrates the possibility of using genetic network analysis combined with bioinformatics to repurpose drugs for the treatment of EC. Further study will investigate the mechanisms of using BCR-ABL1 and AR targeting in the treatment of EC.